World Development Report 1985 - World Bank.; World Bank. (Washington, D.C. The World Bank, 1985)
This report focuses on the contribution that international capital makes to economic development. While the report pays close attention to the events of the recent past, it also places the use of foreign capital in a broader and longer-term perspective. Using such a perspective, the report shows how countries at different stages of development have used external finance productively; how the institutional and policy environment affects the volume and composition of financial flows to developing countries; and how the international community has dealt with financial crises. This report concludes that the developing countries will have a continuing need for external finance. It demonstrates that many of the policies required to attract external finance and promote economic growth are either being implemented or planned already.
Electronic reproduction.
Keywords: Economic assistance; Underdeveloped areas -- Economic conditions; Underdeveloped areas -- Economic indicators; Electronic books